Well, when you get the antiderivative, you can put in the limits and get
$ \begin{array}{l}
\lim\limits _{x\rightarrow \infty }[ x-ln( cosh( x))] =\lim\limits _{x\rightarrow \infty }\left[\frac{( x+ln( cosh( x)))( x-ln( cosh( x)))}{( x+ln( cosh( x)))}\right] =\lim\limits _{x\rightarrow \infty }\left[\frac{x^{2} -ln^{2}( cosh( x))}{x+ln( cosh( x))}\right]\\
=\lim\limits _{x\rightarrow \infty }\left[\frac{x^{2}}{x+ln( cosh( x))} -\frac{ln^{2}( cosh( x))}{x+ln( cosh( x))}\right] =\lim\limits _{x\rightarrow \infty }\left[\frac{2x}{1+tanh( x)} -\frac{2tanh( x) ln( cosh( x))}{1+tanh( x)}\right]\\
\\
\lim\limits _{x\rightarrow \infty }[ x-ln( cosh( x))] =\lim\limits _{x\rightarrow \infty }\left[ 2\frac{x-tanh( x) ln( cosh( x))}{1+tanh( x)}\right]\\
This\ means\ it\ equals\ itself,\ because\ tanh( \infty ) =1
\end{array}$
After that, I was stuck... But maybe this will help you; or someone else to answer your problem.
But I do know that
\lim\limits _{x\rightarrow \infty }[ x-ln( cosh( x))] =ln( 2)
I just don't know how.